Swedes in Michigan - Mead, Rebecca J. (Discovering the peoples of Michigan., 2012)
In the late nineteenth and early twentieth centuries, large numbers of Swedish immigrants came to Michigan seeking new opportunities in the United States and relief from economic, religious, or political problems at home. In addition to establishing early farming communities, Swedish immigrants worked on railroad construction, mining, fishing, logging, and urban manufacturing. As a result, Swedish Americans made significant contributions to the economic and cultural landscape of Michigan, a history this book explores in engaging and illustrative depth. Swedes in Michigan traces the evolution of hard-working people who valued education and assimilated actively while simultaneously maintaining their cultural ties and institutions. Moving from past to present, the book examines community patterns, family connections, social organizations, exchange programs, ethnic celebrations, and business and technical achievements that have helped Swedes in Michigan maintain a sense of their heritage even as they have adapted to American life.